Monensin levels in a steam-flaked milo finishing diet with 4% added fat - Robert T. Brandt Jr.; S.J. Anderson; J.K. Elliott (Kansas Agricultural Experiment Station Research Reports, 1991)
Response to monensin (Control, 12.5, or 25 g/ton, air dry basis) by yearling steers fed a diet with 4% added fat was evaluated. For the entire study (104 d), daily gain, feed consumption and feed efficiency were unaffected (P>.25) by monensin. These results are in general agreement with some of our previous reports of diminished animal response to ionophores in fat-supplemented finishing diets. No adverse effects on animal health have been observed in our studies. However, whether withdrawing ionophores from finishing rations with 3.5-4% fat will affect the incidence of digestive upsets in commercial applications is not clear.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Monensin level; Fat; Cattle; Feedlot performance